The Representation of Woman Character in the Movie of Enola Holmes - Yuliana, Fitri; Margana, Margana; Triyono, Sulis (Indonesian literature Program, Faculty of Humanities, Diponegoro University, 2025)
Women have constructs formed by society. The construct can not only be seen in the real world, but it can also be seen through stories in the media where these stories are also caused by public beliefs. The objective of this research is to discover the representation of women found in the movie of Enola Holmes which is seen from the perspective of male and female characters. In addition, this research also aims to look at the subject-object position and reader position by applying Mills’ Feminist Stylistics theory as the analytical framework. This research used a qualitative method as a research design. This research also used the movie of Enola Holmes to find the representation of women. The data used are words, sentences, and discourses spoken by male and female characters that describe a woman. The data obtained are examined using the theory proposed by Sara Mills. This research found that women are still often regarded as lower than men.